The Archives Management System in the General Affairs and Human Resources Division at the Langsa City Regional Secretariat Office - Erni Wiriani (Yayasan Putra Adi Dharma, 2024)
The research conducted examines the archive management system in the General Affairs and Personnel Section of the Secretariat of the Langsa City Regional Government. Data collection was obtained through field observations and research related to existing facilities, human resources, and systems in archive management. Facilities are adequate, including filing cabinets, archive shelves, and archive cabinets, but there is a lack of employees with educational backgrounds in archive management. The archive management system consists of storage, borrowing, retrieval, maintenance, transfer, and disposal of archives. There are several shortcomings in the archive storage and retrieval process caused by the lack of thoroughness of the personnel. Efforts made in archive maintenance are relatively simple, there are retention schedules for archive transfer and disposal, but there is a challenge with the large volume of archives. There is a need for improvement in human resource management and a review of the archive management process to ensure the smoothness and effectiveness of the system.